Akurasi COVID-19 Rapid Mortality Surveillance dalam Menentukan Dugaan Sebab Kematian akibat COVID-19 - Ravenna Salva Zahira; Citra Manela; Arni Amir; Netti Suharti; Elmatris Syamsir (CV. ITTC INDONESIA, 2026)
Background: COVID-19 Rapid Mortality Surveillance (CRMS) is a tool designed to differentiate suspected COVID-19-related deaths from other cause. Identifying the cause of death—particularly in relation to COVID-19—is crucial for understanding the epidemiology of the disease and for planning public health and safety. Objective: This study aimed to evaluate the accuracy of the COVID-19 Rapid Mortality Surveillance (CRMS) in determining suspected COVID-19-related death at Dr. M. Djamil Hospital, Padang. Methods: This study was a descriptive observational study involving 78 deceased patients, both COVID-19 and non-COVID-19 cases, at Dr. M. Djamil Hospital in 2021. Data were collected through interviews with the patients' family members. Accuracy was analyzed using receiver operating characteristic (ROC) curve analysis and 2×2 contingency table analysis. Results This study indicates that the most common gender of entire sample was female and the age group was >65 years old. The CRMS demonstrated a sensitivity of 84.2%, specificity of 85%, positive predictive value of 72.7%, negative predictive value of 91.9%, overall accuracy of 84.7%, and an area under the ROC curve (AUC) of 0.926. Conclusion: The CRMS shows high accuracy in identifying suspected COVID-19-related death.